A NEW APPROACH OF COMPOSITIONAL SIMULATION FOR A VOLATILE OIL RESERVOIR MODELING - Ego Syahrial (Scientific Contributions Oil and Gas, 2010)
This paper proposes a new compositional simulation approach for a volatile oil reservoirmodelling. The proposed formulation has an implicit equation for the oil-phase pressureand water saturation, an explicit equation for the hydrocarbon saturation, and explicitequation for the overall composition of each hydrocarbon component that satisfiesthermodynamic equilibrium. An Equation of State for phase equilibrium and property calculationsis used in this new formulation. Interfacial tension effects are included in thisapproach to characterise the thermodynamically dynamic nature of the relative permeability.A two-dimensional relative permeability algorithm is included which handles lumpedhydrocarbon phase hydrocarbon phase as well as individual phase flows. For each gridblock two equations are required, namely total hydrocarbon and water-phase flow equations.These equations are highly non-linear and they are linearised by using Newton-Raphson method. The resulting equations are solved by an efficient Conjugate Gradientbased iterative technique to obtain pressures and saturations simultaneously, and hydrocarbon-phase saturations are deduced from their respective equations.The new compositional simulation approach is validated through analytical and numericalmethods. It is demonstrated in this present paper that the results are comparedfavourably with analytical techniques and published numerical results. They also confirmthat the proposed codified formulation is unconditionally stable and it is as stable as fullycompositional model yet the computational cost reduction was substantial.